2023
DOI: 10.2147/ccid.s409621
|View full text |Cite
|
Sign up to set email alerts
|

TET2 Promotes Keloid Hyperplasia by Regulating 5hmC Modification in the TGFβ Promoter Region

Abstract: Introduction As a kind of human unique benign skin tumour, keloid has caused great trouble to the physical and mental health of patients and is unfavourable for beautiful. The abnormal proliferation of fibroblasts is one of the main causes of keloid formation. TET2 (Ten eleven translocation 2) catalyzes the oxidation of cytosine 5mC to 5hmC which process plays important role in cell proliferation. However, the molecular mechanism of TET2 in keloids is not well-researched. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Niu et al . found that overexpression of DNMT3A inhibited TGF-β expression by decreasing 5hmC, which is located in the TGF-β promoter region, thus inhibiting fibroblast proliferation [ 49 ]. Recently, increasing attention has been given to m 6 A methylation, which is a posttranscriptional modification of eukaryotic mRNAs and lncRNAs [ 50 ].…”
Section: Genetic and Epigenetic Regulation Of Keloidsmentioning
confidence: 99%
“…Niu et al . found that overexpression of DNMT3A inhibited TGF-β expression by decreasing 5hmC, which is located in the TGF-β promoter region, thus inhibiting fibroblast proliferation [ 49 ]. Recently, increasing attention has been given to m 6 A methylation, which is a posttranscriptional modification of eukaryotic mRNAs and lncRNAs [ 50 ].…”
Section: Genetic and Epigenetic Regulation Of Keloidsmentioning
confidence: 99%